The effect of educational exercises to learn the grip of the balance in developing the motor balance and agility of Al Hurra wrestlers, ages (14-16) years (Journal of the College of Basic Education, 2020)
The trainers should take care of the aspects that affect the performance of the wrestlers in the wrestling, including the motor abilities of balance and agility because of the direct impact on the process of achieving a good level of performance in these controls by young wrestlers, and varied educational and training curricula because of the great impact in The preparation of wrestlers is all-round because of their great impact in winning the win that results in wrestling.The research aims to identify:1 - Preparation of educational exercises to learn the balance in the development of balance of kinetic and agility of free wrestlers fit the capabilities of the sample research.2 - to recognize the impact of educational exercises to learn balance in the development of balance of motor and agility for the free entrepreneurs.The experimental method was used and the sample of the research was selected from Al-Athamiya Sports Club's youth group which is (8) wrestlers. The results showed that the use of educational exercises by the researcher has positively affected the improvement of motor equilibrium in free wrestlers. It has been recommended that educational and training programs should be used to develop balance and fitness while taking into consideration the technical aspects of movement or grip.